2021
DOI: 10.1021/acsnano.1c05738
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Tunable Synthesis and Etching-Free Transfer of Two-Dimensional Magnetic FeTe

Abstract: Two-dimensional (2D) Fe-chalcogenides (e.g., FeS, FeSe, and FeTe, etc.) have sparked extensive interest due to their rich phase diagrams including superconductivity, magnetism, and topological state, as well as versatile applications in electronic devices and energy related fields. However, the phase-tunable synthesis and green transfer of such fascinating materials still remain challenging. Herein, we develop a temperature-mediated chemical vapor deposition (CVD) approach to grow ultrathin nonlayered hexagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 51 publications
(89 reference statements)
1
55
0
Order By: Relevance
“…Etching-free transfer and of 2D metallic p-doped SnSe nanosheets. The PVD-synthesized 2D metallic p-doped SnSe nanosheets were transferred by using the polystyrene assistant method 39 . The morphology, domain size, thickness, phase structure, optical property, and crystalline quality of 2D metallic p-doped SnSe nanosheets were characterized by OM (Olympus BX53M), AFM (Dimension Icon, Bruker), XPS (Thermo Scienti c K-Alpha+ system, and the binding energies were calibrated by C1s at ~284.8 eV), XRD (Rigaku Smartlab SE), Raman spectroscopy (Renishaw, with the excitation light of ~532 nm), and TEM (JEOL JEM-F200, with the acceleration voltage of ~200 kV).…”
Section: Methodsmentioning
confidence: 99%
“…Etching-free transfer and of 2D metallic p-doped SnSe nanosheets. The PVD-synthesized 2D metallic p-doped SnSe nanosheets were transferred by using the polystyrene assistant method 39 . The morphology, domain size, thickness, phase structure, optical property, and crystalline quality of 2D metallic p-doped SnSe nanosheets were characterized by OM (Olympus BX53M), AFM (Dimension Icon, Bruker), XPS (Thermo Scienti c K-Alpha+ system, and the binding energies were calibrated by C1s at ~284.8 eV), XRD (Rigaku Smartlab SE), Raman spectroscopy (Renishaw, with the excitation light of ~532 nm), and TEM (JEOL JEM-F200, with the acceleration voltage of ~200 kV).…”
Section: Methodsmentioning
confidence: 99%
“…The size of the prepared nanocrystal can be over 100 μm, which makes it easy to pattern electrodes on the sample and study electrical properties on the single nanocrystal level. Shi et al also reported the growth of 2D magnetic FeTe nanocrystals on mica substrate . The prepared sample can be as thin as 2.3 nm and as large as 120 μm.…”
Section: Synthesis Of 2d Magnetic Tmcsmentioning
confidence: 97%
“…There are a variety of unique stoichiometric ratios, such as FeSe, FeSe 2 , Fe 3 Se 4 , Fe 7 Se 8 , FeTe, and FeTe 2 . Even in the same composition, multiple phases could exist, for example, hexagonal and tetragonal FeTe. ,, The complicated structures in the iron chalcogenides form the basis of rich magnetic properties, where the exchange function between the iron ions can be altered in different structures. So far, only Fe 7 Se 8 , FeSe 2 , FeTe, and FeTe 2 have been prepared by the current solid-precursor-based CVD method. ,, Hexagonal FeSe 2 and FeTe 2 are layered materials, where each Fe atom plane is sandwiched by two Se or Te atom planes (Figure a–d). , Besides, tetragonal FeTe also adopts layered structures, which comply with a P 4 g wallpaper group symmetry, as shown in the atomic model and zoom-in STEM image in Figure e–i. The rest, including Fe 7 Se 8 and hexagonal FeTe, are all intrinsically nonlayered materials (Figure j–n). , The CVD method enables the preparation of ultrathin nonlayered nanomaterials, making it possible to study the thickness-dependence of magnetic properties in these materials.…”
Section: Structures Of 2d Magnetic Tmcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the PS/Fe 7 S 8 was soaked in toluene to dissolve PS and then blown dry by nitrogen gas. The etching-free method was also employed to transfer CVD-synthesized FeTe nanosheets …”
Section: Experimental Sectionmentioning
confidence: 99%